2021
DOI: 10.3390/rs13132456
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamical Structure of a Warm Core Ring as Inferred from Glider Observations and Along-Track Altimetry

Abstract: This study investigates the vertical structure of the dynamical properties of a warm-core ring in the Gulf of Mexico (Loop Current ring) using glider observations. We introduce a new method to correct the glider’s along-track coordinate, which is, in general, biased by the unsteady relative movements of the glider and the eddy, yielding large errors on horizontal derivatives. Here, we take advantage of the synopticity of satellite along-track altimetry to apply corrections on the glider’s position by matching … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
2
4
1
Order By: Relevance
“…Consistent with previous ship and glider observations of individual LCRs [7,27], the typical LCR is characterized by a warm temperature anomaly with weaker stratification, and a double core salinity structure, with a fresher anomaly near the surface and a high salinity anomaly between 150 and 300 m. Although typical LCRs are large eddies, we found that the gradient-wind-balanced velocity was significantly larger than the geostrophic velocity (≈ +20% between the rotation axis and the maximum velocity radius), similar to Meunier et al's [30] recent observation in LCR Poseidon. This results in an increased relative vorticity, reaching half of the Coriolis frequency, showing that average LCRs (medium size) are significantly non linear eddies with a Rossby radius of 0.5.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Consistent with previous ship and glider observations of individual LCRs [7,27], the typical LCR is characterized by a warm temperature anomaly with weaker stratification, and a double core salinity structure, with a fresher anomaly near the surface and a high salinity anomaly between 150 and 300 m. Although typical LCRs are large eddies, we found that the gradient-wind-balanced velocity was significantly larger than the geostrophic velocity (≈ +20% between the rotation axis and the maximum velocity radius), similar to Meunier et al's [30] recent observation in LCR Poseidon. This results in an increased relative vorticity, reaching half of the Coriolis frequency, showing that average LCRs (medium size) are significantly non linear eddies with a Rossby radius of 0.5.…”
Section: Discussionsupporting
confidence: 89%
“…The average LCR's PV structure consists of a bowl of low PV deflecting the main pycnocline's high PV strip downwards, and is mostly controlled by density stratification. It should be pointed out that the average LCR computed here has a weaker PV anomaly, with a lesser vertical extension, than the recent observations of Meunier et al [30] of LCR Poseidon. We stress this is related to the exceptionally thick thermostadt observed in Poseidon, while the work is focused on describing an average LCR.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations